Impact of Plant Growth Regulators on Yield and Yield Components in Rice (Oryza sativa L.) Under Field Conditions - Soomro, Abdul Samad; Soomro, Abdul Sattar; Mazari, Shabana Naz (International Journal of Applied Sciences and Biotechnology, 2020)
The exercise of using (PGRs), especially Gibberellic acid and in field of agriculture has become commercialized in some of the country including Pakistan. Number of different crops are being treated by farmers mostly vegetables; currently evaluated in rice crop through foliar application at different intervals to evaluate their efficiency at different doses. Results revealed that there was no significant difference in crop maturity compared with control. Plant height was variable among treated plots, highest plant height was recorded (121.2cm) in 2017-18 experiment in T-3 Gibberellic acid @ 12grams/acre while minimum (96.2cm) in 2016-17 in T-7 Control. Tillers/hill was increased, and maximum counted 18.5/hill in T-3 Gibberellic acid @ 10gms/acre whereas 11.9/hill was recorded in T-7 Control. Grain filling was obvious recorded with significance; counted 83 percent in T-5 Naphthalene acetic acid treated 100ml/acre whereas average minimum (71.3%) was recorded in T-7 Control. Not only plant development was modified by the treatments but yield was also increased average maximum (3228kgs/acre) with 19.61 percent was recorded in T-5 Naphthalene acetic acid @ 100ml/acre. Int. J. Appl. Sci. Biotechnol. Vol 8(3): 318-322